The role of artificial intelligence applications in business - Masa'deh, Ra'ed (Technological innovation and sustainability for business competitive advantage ;, 2025)
Artificial Intelligence applications play a crucial role in modern businesses across various industries. The Role of Artificial Intelligence Applications in Business examines key aspects of how digital technologies impact businesses, including AI-powered chatbots, self-service portals, and online customer support systems which can help enhance the overall customer experience. In addition, digital technologies enable businesses to collect and analyse vast amounts of data (big data analytics). This data provides valuable insights into customer behaviour, market trends, and operational performance, thereby helping businesses make informed decisions and personalise their offerings. Moreover, automation and digital tools help streamline processes, and reduces manual efforts and errors. For instance, project management software, CRM systems, and ERP solutions optimise workflows, leading to increased efficiency and productivity. Digital marketing channels such as social media, search engine optimization (SEO), and online advertising allow businesses to reach their target audience more effectively and at a lower cost compared to traditional methods. Personalised marketing campaigns based on data analysis further enhance customer engagement. Digital technologies have transformed the way businesses sell products and services. The book will help readers in understanding the role of artificial intelligence in promoting business and management success. Fulfilling a growing need for aligning business strategy and educational curriculums with the evolving skills required for business workplaces Technological Innovation and Sustainability for Business Competitive Advantage presents a thorough understanding of how business, education and technology can enable current and future leaders to contribute positively to the digital transformation currently in play across the globe.